2002
DOI: 10.1080/01411920120122185
|View full text |Cite
|
Sign up to set email alerts
|

Educational Motivation and Engagement: Qualitative accounts from three countries

Abstract: This article extends and develops earlier survey studies by reporting ndings from detailed interviews with adolescents in Sunderland, Kentucky and St Petersburg. The interviews sought to examine a number of key factors underpinning educational motivation and engagement, in particular, attitudes about schooling, self-evaluations of academic performance, patterns and rate of work at home and at school, reasons why education may be valuable and aspirations for the future. A number of reasons for the presence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
5
36
0
Order By: Relevance
“…Accordingly to Schlechty (2002), this classroom can be termed as a highly engaged one as most of the students are authentically engaged most of the time, and all of the students are authentically engaged at least some of the time (Schlechty, 2002).This study supports and extends previous research (Bryson & Hand, 2007;Deci, Koestner, & Ryan, 1999;Haberman, 1991;Hufton et al, 2002;Martin, 2003;Munns & Martin, 2005;Murray et al, 2004;Patall, Cooper & Robinson, 2008;Reeve et al, 2004;Ryan,2000;Schlechty, 2002;Schmakel, 2008;Shernoff, Csikszentmihalyi, Schneider & Shernoff, 2003;Smyth & McInereny, 2007;Steele & Fullagar, 2009;Tadich et al, 2007;Willms, 2003;Zyngier, 2007) suggesting that good teacher-student relationship; clear instructions; group work; giving choice, planning engaging and interesting learning activities; and making learning important and valuable to students all contribute to promoting and enhancing student motivation and engagement in their learning.…”
Section: Discussionsupporting
confidence: 81%
“…Accordingly to Schlechty (2002), this classroom can be termed as a highly engaged one as most of the students are authentically engaged most of the time, and all of the students are authentically engaged at least some of the time (Schlechty, 2002).This study supports and extends previous research (Bryson & Hand, 2007;Deci, Koestner, & Ryan, 1999;Haberman, 1991;Hufton et al, 2002;Martin, 2003;Munns & Martin, 2005;Murray et al, 2004;Patall, Cooper & Robinson, 2008;Reeve et al, 2004;Ryan,2000;Schlechty, 2002;Schmakel, 2008;Shernoff, Csikszentmihalyi, Schneider & Shernoff, 2003;Smyth & McInereny, 2007;Steele & Fullagar, 2009;Tadich et al, 2007;Willms, 2003;Zyngier, 2007) suggesting that good teacher-student relationship; clear instructions; group work; giving choice, planning engaging and interesting learning activities; and making learning important and valuable to students all contribute to promoting and enhancing student motivation and engagement in their learning.…”
Section: Discussionsupporting
confidence: 81%
“…Motivation is a psychological construct and is not synonymous with the actual behaviours involved in a particular activity (Hufton et al, 2002). While historically prevalent views assume that motivation is an integral component of all learning (Harlen & Deacon Crick, 2002;Torrance & Coultas, 2004), there is a growing body of literature to suggest that what motivates some students may alienate others (Harlen & Deacon Crick, 2003).…”
Section: Was Struck By the Irony That I Did An Enormous Amount Of Rmentioning
confidence: 99%
“…This perceived authenticity also seems to have impacted on their enjoyment. The fact that the experience was enjoyable is important, not least because research has shown that enjoyment is connected with motivation (Hufton, Elliott, and Illushin 2002;Waite and Davis, 2006). It is also claimed that this positive feeling or atmosphere improved the quality of their music: "It sounded really cool because I've never really been good at music, it ends up like breaking, with the guitar ending up coming out of tune or something.…”
Section: The Acoustics Of the Locationmentioning
confidence: 99%